2016
DOI: 10.1103/physrevaccelbeams.19.030401
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 5-MA 100-ns linear-transformer-driver accelerator for wire array Z-pinch experiments

Abstract: The linear-transformer-driver (LTD) is a recently developed pulsed-power technology that shows great promise for a number of applications. These include a Z-pinch-driven fission-fusion-hybrid reactor that is being developed by the Chinese Academy of Engineering Physics. In support of the reactor development effort, we are planning to build an LTD-based accelerator that is optimized for driving wire-array Z-pinch loads. The accelerator comprises six modules in parallel, each of which has eight series 0.8-MA LTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…The composition of these charging resistors has not been reported previously. This type of resistor, patented by Stoltzfus et al [45], was invented to provide highimpedance with long-term stability and to avoid the problems that arise when using aqueous resistors, such as copper sulfate, in high-power LTDs [16,34,42,46]. Aqueous resistors are known to permeate water through their plastic housings contaminating the cavity and at the same time creating air bubbles inside the resistor that can dramatically change the impedance of the resistor and even create breakdowns inside the resistor.…”
Section: A Charging Circuitmentioning
confidence: 99%
See 3 more Smart Citations
“…The composition of these charging resistors has not been reported previously. This type of resistor, patented by Stoltzfus et al [45], was invented to provide highimpedance with long-term stability and to avoid the problems that arise when using aqueous resistors, such as copper sulfate, in high-power LTDs [16,34,42,46]. Aqueous resistors are known to permeate water through their plastic housings contaminating the cavity and at the same time creating air bubbles inside the resistor that can dramatically change the impedance of the resistor and even create breakdowns inside the resistor.…”
Section: A Charging Circuitmentioning
confidence: 99%
“…Previous work exists where monolithic solid resistors were used in place of conventional aqueous resistors but it was found that these would occasionally disintegrate or degrade [34,46]. Recent work has also been done by Zhou et al [16] that uses wirecoil "spring" inductors instead of aqueous resistors for charging and triggering.…”
Section: A Charging Circuitmentioning
confidence: 99%
See 2 more Smart Citations
“…Circuit simulation tools are usually used to estimate the operating parameters such as peak voltage, pulse duration and amplitude of conduction current for each component in the induction cavity [21,22]. They provide the designing criteria for each component.…”
Section: Introductionmentioning
confidence: 99%